Trade wars between the United States of America (USA) and the People’s Republic of China (PRC) in the Trump era (2018-2020) - Haskan, Sinan (My University, 2021)
The President of the United States of America (USA) Donald J. Trump, in February 2018, began to additional customs tariffs on the imports of various products from the People's Republic of China (PRC) to reduce the bilateral trade deficit with the PRC; because the Trump administration considered this imbalance as the largest source of the USA’s current account deficit. In April of the same year, the protectionist policies implemented by the two countries became a trade war when the Beijing government started to implement additional customs tariffs on some products imported from the USA. However, the fact that there has not been a severe change in the trade deficit between the two countries in the process from 2018, when the trade wars began, to the Phase-1 Deal signed in 2020, is quite remarkable. This case indicates that there are reasons different from the current account deficit or the bilateral trade deficit under the rising tension between both countries. From this point of view, this thesis reveals that the main reason underlying the USA-PRC trade wars is based on the rivalry between the two states to be a hegemonic power in the international arena. In this context, commercial, technological, industrial, and geopolitical policies, which form a side of this friction, are analyzed in order to discuss the different aspects of the process. ÖZET……………………………………………………………………………………ii ABSTRACT…………………………………………………………………………iii ACKNOWLEDGEMENTS…………………………………………………iv TABLE OF CONTENTS……………………………………………………v ABBREVIATIONS…………………………………………vii LIST OF TABLES…………………………………………ix LIST OF GRAPHICS……………………x 1. INTRODUCTION………1 1.1. TRUMPONOMICS AND THE PROTECTIONISM IN THE USA AGAINST CHINA:..............................2 1.2. LITERATURE REVIEW…..…....5 1.3. RESEARCH QUESTION AND METHODOLOGY……19 1.4. STRUCTURE OF THE THESIS…………………………21 2. THEORETICAL AND CONCEPTUAL DEBATES ON TRADE WARS………………………….23 2.1. TRADE WARS: A CONCEPTUAL INTRODUCTION…..................23 2.2. THE RELATIONSHIP BETWEEN PROTECTIONISM AND HEGEMONY: A HISTORICAL PERSPECTIVE..................…27 2.3. TRADE WARS IN THE HISTORY……………31 2.3.A. SMOOTH-HAWLEY ACT……………………………………31 2.3.B. CURRENCY WARS………………..32 2.3.C. THE USA-JAPAN TRADE WAR……….39 2.3.D. OTHER TRADE WAR EXAMPLES FROM HISTORY.....…..41 3. TRADE WAR BETWEEN THE USA AND CHINA FROM 2018 TO 2020………………………………………………………………………………………………………..42 3.1. GENERAL PERSPECTIVES OF THE COUNTERPARTIES IN THE TRADE WAR BETWEEN USA AND CHINA..................42 3.1.1. THE ASSERTIONS AND JUSTIFICATIONS OF USA…………………………………...……42 3.1.2. RESPONSES OF CHINA TO THE USA CLAIMS AND OFFICIALLY LAUNCHING OF THE USA-CHINA TRADE WAR..……..................................................46 3.2. ECONOMIC RESULTS OF THE USA-CHINA TRADE WAR: IN THE FACE OF THE AIM AT REDUCING OF BILATERAL TRADE DEFICIT PROFIT OR LOSS?......................................................................50 3.3. THE ACTUAL MEANING OF THE USA-CHINA TRADE WARS: POLITICAL CONCERNS BEHIND ECONOMIC REASONS……………56 3.3.1. CURRENCY POLICY AND MERCANTILISM DEBATES DURING THE USA-CHINA TRADE WARS: CHINA’S RISING………………….57 3.3.2. TECHNOLOGICAL COMPETITION BETWEEN THE USA AND CHINA: MADE-INCHINA 2025 (MiC 2025)…………61 3.3.3. INTERNATIONALIZATION OF RENMINBI (RMB): CHINA’S ALTERNATIVE TO THE GLOBAL POSITION OF US DOLLAR (USD)………………………….68 3.3.4. THE BASIC RATIONALE OF TRADE WARS: CHINA’S GEOPOLITICAL AND HEGEMONIC CHALLENGE WITH THE USA………………………75 4. CONCLUSION………………………………………………………...…………………85 5. BIBLIOGRAPHY………………………………………………………..……………………….98 APPENDIX: THE TIMELINE OF THE USA-CHINA TRADE WARS UP TO THE PHASE-1 DEAL.............122

Amerika Birleşik Devletleri (ABD) Başkanı Donald J. Trump, Şubat 2018'de, ABD'nin cari açığının en büyük kaynağı olarak değerlendirdiği Çin Halk Cumhuriyeti (ÇHC)’nden ithal edilen çeşitli ürünler için ikili ticaret açığının büyüklüğünü de gerekçe göstererek ek gümrük tarifesi uygulamaya başladı. Aynı yılın Nisan ayında Pekin yönetimince benzer şekilde ABD'den ithal edilen bazı ürünler için ek gümrük tarifelerinin yürürlüğe girmesiyle iki ülke tarafından izlenmeye başlanan korumacı politikalar bir ticaret savaşı halini almıştır. Bununla birlikte, ticaret savaşlarının başladığı 2018 yılından 2020 yılında imzalanan Faz-1 Anlaşmasın'na kadar gelişen süreçte iki ülke arasındaki ticaret açığında ciddi bir değişikliğin meydana gelmemiş olması oldukça dikkat çekici olup yükselen gerilimin arkasında cari açık veya ikili ticaret açığından farklı nedenler olduğuna işaret etmektedir. Bu noktadan hareketle, bu tezde, ABD ve ÇHC arasında ortaya çıkan ticaret savaşlarının altında yatan esas nedenin iki ülke arasında uluslararası arenada hegemon güç olma rekabetine dayandığı ortaya konmaktadır. Bu bağlamda, iki ülke arasında yaşanan sürtüşmeye konu olan ticari, teknolojik, endüstriyel politikalar ile jeopolitik gelişmeler analiz edilerek süreç ele alınmıştır.
Keywords: ABD; Balance of Payments; Cari Açık; China; Commercial policy; Currency Manipulation; Current Deficit; ÇHC; Çin; Finance; Geopolitics ABD; Hegemony; Hegemonya; Jeopolitik; Korumacılık; Kur Manipülasyonu; Maliye; Ödemeler Dengesi; PRC; Protectionism; Technology; Teknoloji; Ticaret Açığı; Ticaret politikası; Ticaret Savaşları; Trade Deficit; Trade Wars; United States; USA